Biometrical and Micrometrical Studies on Gall Bladder of Sheep During Prenatal and Postnatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on gall bladder of fetuses (n= 30) of 40 days’ old (2.0 cm crown anus length CAL) to postnatal sheep (n=10) below one year of age without any external anomaly to investigate the biometrical and micrometrical changes during prenatal and postnatal development. The prenatal gall bladder were divided into three groups comprised of ten samples in each group according to the gestational age viz. Group I (0-50), Group II (51-100), Group III (101-150) days of gestation and Group IV comprised of sheep below one year of age. A progressive increase in length and width of gall bladder and length and diameter of cystic duct were observed both in prenatal and postnatal periods with advancing age. There was a positive correlation between height ofepithelium, thickness of lamina propria submucosa, tunica muscularis and tunica serosa of gall bladder with increase in gestational age and post natal development.